2017
DOI: 10.3390/molecules22091573
|View full text |Cite
|
Sign up to set email alerts
|

Sulfadiazine Salicylaldehyde-Based Schiff Bases: Synthesis, Antimicrobial Activity and Cytotoxicity

Abstract: The resistance among microbes has brought an urgent need for new drugs. Thus, we synthesized a series of Schiff bases derived from the sulfa drug sulfadiazine and various salicylaldehydes. The resulting 4-[(2-hydroxybenzylidene)amino]-N-(pyrimidin-2-yl)benzene-sulfonamides were characterized and evaluated against Gram-positive and Gram-negative bacteria, yeasts, moulds, Mycobacterium tuberculosis, nontuberculous mycobacteria (M. kansasii, M. avium) and their cytotoxicity was determined. Among bacteria, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 21 publications
3
38
0
2
Order By: Relevance
“…Furthermore, a prominent peak appears in the spectra of Schiff base at 1654 cm −1 confirmed the formation of an imine (CN) linkage. Similar peaks were found in the literature of the Schiff base compounds …”
Section: Resultssupporting
confidence: 87%
“…Furthermore, a prominent peak appears in the spectra of Schiff base at 1654 cm −1 confirmed the formation of an imine (CN) linkage. Similar peaks were found in the literature of the Schiff base compounds …”
Section: Resultssupporting
confidence: 87%
“…These substituents provide both wide-spectrum antibacterial activity and comparatively low MIC values. Interestingly, similar results were obtained for sulfadiazine Schiff bases previously [20]. MIC of 5-nitrofurfural-derived Schiff base 1r (62.5-125 µM, i.e., 16.25-32.51 µg/mL) is fully comparable to breakpoint of its clinically used analogue nitrofurantoin for staphylococci (32-64 µg/mL) according to EUCAST [33].…”
supporting
confidence: 82%
“…Previously, we have applied molecular hybridization approach successfully. Illustratively, salicylaldehyde-based imines and hydrazones derived from known bioactive scaffolds (Figure 2, XIII-XIV) have exhibited a significant antimicrobial activity [19][20][21]. We have described that a potent antimicrobial activity is associated only with the salicylidene moiety and its isomers are substantially less active [21,22].…”
Section: Figurementioning
confidence: 97%
“…Many of the Schiff base metal complexes act as antifungal, antibacterial [7], antiviral [8], herbicidal [9], analgesic [10], anti-inflammation [11,12], antioxidant [6,13], antitumor [14,15], anticancer [16,17], antitubercular [18][19][20] agent. Previously, many investigations have been demonstrated that, Schiff base with aromatic and hetarocyclic ring coordinated with transitional metals show potential activity against MTB and different microorganisms [18,[20][21][22][23][24], suggesting new possible candidate to break the resistant of MTB. Synthesis, characterization and biomedical application of our investigated ligands and complexes were reported in our previous work [25].…”
Section: Introductionmentioning
confidence: 99%